Genotype Independent Regeneration and Agrobacterium?mediated Genetic Transformation of Sweet Potato (Ipomoea batatas L.) - Shekhar, Shubhendu; Agrawal, Lalit; Buragohain, Alak Kumar; Datta, Asis; Chakraborty, Subhra; Chakraborty, Niranjan (Plant Tissue Culture and Biotechnology, 2013)
Development of an efficient genotype independent regeneration and genetic transformation system in sweet potato continues to be of great interest. Agrobacterium?mediated genetic transformation protocol was established in two different cultivars of sweet potato using Agrobacterium strain EHA105 harbouring binary plasmid pBI121 containing GUS and nptII genes. The internodal stem segments from 30?day?old micropropogated plants were used as explant with different combinations of media and hormones. MS and LS media with various concentrations of growth regulators proved to be non?responsive and the infecundity was severe with the addition of cytokinins. Nonetheless, MS with 2,4?D and TDZ gave a good percentage of callusing but with low differentiation. In different concentrations of NAA, significant amount of callusing was observed but percentage of rooting remained low in both the genotypes. Gamborgs B5 supplemented with NAA proved to be the most suitable media and hormone combination, which yielded shoot formation after 8 ? 10 weeks with a regenera? tion efficiency of 40 ? 70%. Stable integration of transgene was confirmed by PCR analysis. Furthermore, qRT?PCR analysis was performed to assess the transcript accumulation in addition to the GUS enzymatic assay in the transgenic lines. Plant Tissue Cult. & Biotech. 23(1): 87?100, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15565 D.O.I. 10.3329/ptcb.v23i1.15565